THE ROLE OF COMMUNITY PHARMACIST IN ASSESSMENT AND MANAGEMENT OF ATOPIC DERMATITIS - Milosavljevic, Jelena D; Nikolic, Milena D (Journal of process management and new technologies, 2018)
This issue is a review of treatment for atopic dermatitis – chronic, recurring inflammatory disorder of the skin. For patients affected to atopic dermatitis, community pharmacist is a healthcare professional well placed to be a source of support and advice. This article aims to analyze the therapeutic outcome of 30 patients who asked for advice from a community pharmacist. Subjects were patients with skin problems that have been targeted by eczema. Pharmacist used a standardized questionnaire in order to collect data. The results shows there is a positive feedback between a favorable therapeutic outcome and a given pharmacist advice. Material and work methods are described and some conclusions are presented in the text bellow.